2004
DOI: 10.1523/jneurosci.1436-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death of Adult-Generated Hippocampal Neurons Is Mediated by the Proapoptotic Gene Bax

Abstract: In the dentate gyrus (DG) of the adult mouse hippocampus, a substantial number of new cells are generated daily, but only a subset of these survive and differentiate into mature neurons, whereas the majority undergo programmed cell death (PCD). However, neither the intracellular machinery required for adult stem cell-derived neuronal death nor the biological implications of the significant loss of these newly generated cells have been examined. Several markers for apoptosis failed to reveal cell death in Bax-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
199
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(214 citation statements)
references
References 59 publications
14
199
0
1
Order By: Relevance
“…Our results show that caspase-3 activation may also be important for programmed death of NPCs in the adult SGZ and SVZ in vivo. Consistent with this idea, programmed cell death in the adult hippocampus is dramatically reduced in Bax-knockout mice [27] and after caspase inhibition in rats. Caspase-8 and -9 are upstream initiators of caspase-3-mediated death in what is considered 'classical' apoptosis [26].…”
Section: Discussionmentioning
confidence: 52%
“…Our results show that caspase-3 activation may also be important for programmed death of NPCs in the adult SGZ and SVZ in vivo. Consistent with this idea, programmed cell death in the adult hippocampus is dramatically reduced in Bax-knockout mice [27] and after caspase inhibition in rats. Caspase-8 and -9 are upstream initiators of caspase-3-mediated death in what is considered 'classical' apoptosis [26].…”
Section: Discussionmentioning
confidence: 52%
“…However, the rescued neurons in the VCG of the ND -/-Bax -/-mice failed to migrate properly, indicating that NeuroD is required for the migration of these neurons. Bax is required for neuronal death in the developing brain (Deckwerth et al, 1996) and in adult neural stem cells (Sun et al, 2004). However, the neural development of the Bax -/-mice was largely normal, except that there were fewer apoptotic neurons in the developing CNS (White et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Excess amounts of proapoptotic Bax in its active form can also directly induce cytochrome c release, resulting in formation of the apoptosome complex composed of Apaf-1, caspase-9, and ATP, triggering cell death (Korhonen et al, 2003;Roucou and Martinou, 2001). From studies using Bax null mutant mice, it has recently been shown that in the adult hippocampus, programmed cell death as well as proliferation, migration, and maturation of adult-generated DG neurons is mainly dependent on Bax (Sun et al, 2004). On the other hand, the neuroprotective effects of fluoxetine in the hippocampus are only recently coming to light.…”
Section: Discussionmentioning
confidence: 99%